2012
DOI: 10.1037/a0026299
|View full text |Cite
|
Sign up to set email alerts
|

Pretend play, creativity, and emotion regulation in children.

Abstract: The aim of this study was to examine relationships among pretend play, creativity, emotion regulation, and executive functioning in children. Pretend play processes were assessed using the Affect in Play Scale (APS), which measures children's cognitive and affective processes, such as organization of a plot or use of emotions. Sixty-one female participants, in kindergarten through fourth grade, were assessed using the APS to measure pretend play ability, a divergent thinking task (the Alternate Uses Test), a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
109
0
22

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 208 publications
(150 citation statements)
references
References 49 publications
14
109
0
22
Order By: Relevance
“…Many recent laboratory studies of creativity (Fink, Grabner, Benedek, & Neubauer, 2006;Hoffmann & Russ, 2012;Russ & Schafer, 2006;Silvia et al, 2008) focus on the AUT. In addition to that task, some studies have also used the Wallach and Kogan (1965) instances task to assess verbal divergent thinking (Benedek, Jauk, Sommer, Arendasy, & Neubauer, 2014;Benedek, Mühlmann, Jauk, & Neubauer, 2013).…”
Section: An Overview Of Divergent Thinking Methodsmentioning
confidence: 99%
“…Many recent laboratory studies of creativity (Fink, Grabner, Benedek, & Neubauer, 2006;Hoffmann & Russ, 2012;Russ & Schafer, 2006;Silvia et al, 2008) focus on the AUT. In addition to that task, some studies have also used the Wallach and Kogan (1965) instances task to assess verbal divergent thinking (Benedek, Jauk, Sommer, Arendasy, & Neubauer, 2014;Benedek, Mühlmann, Jauk, & Neubauer, 2013).…”
Section: An Overview Of Divergent Thinking Methodsmentioning
confidence: 99%
“…In this sense, a neighborhood stickball game affords the context through which children might imagine themselves as Major League Baseball players competing in the World Series. Within this type of fantasy play, children are able to engage in the cognitive processes that facilitate the development of creativity through the integration of reality and imagination, a notion supported by Hoffmann and Russ (2012), who found a significant relationship between forms of pretend play and creativity as measured via divergent thinking and storytelling.…”
Section: Sport As Play Play As Creativitymentioning
confidence: 96%
“…For example, Hoffman and Russ' (2012) correlational study on pretend play, divergent thinking, storytelling, emotion regulation, and executive functioning revealed that pretend play is associated with creativity in the forms of divergent thinking and storytelling. Their research also points to a positive relationship between affect and creativity.…”
mentioning
confidence: 98%